Philornis downsi (Diptera: Muscidae), an avian nest parasite invasive to the Galápagos Islands, in Mainland Ecuador - Bulgarella, Mariana (2015)
Philornis downsi (Dodge and Aitken) is a bird-parasitic muscid fly native to mainland South America that recently invaded the Galápagos Islands where it is parasitizing Darwin's finches and other land birds. This parasite was previously known only from Argentina, Brazil, and Trinidad and Tobago. The first report of P. downsi from mainland Ecuador is provided, supporting the hypothesis that the invasion route of P. downsi from its native range to the Galápagos Islands includes mainland Ecuador. Four different morphologies of pupal exuviae, which belong to different fly species, were uncovered. Dipteran puparia were found in 20% of naturally occurring nests collected in 2013 and in 27% of nests in 2014 at the two sites in western Ecuador. P. downsi accounted for 74% and 40% of the puparia in 2013 and 2014, respectively. Two new bird host species for the genus Philornis were recorded: the streak-headed woodcreeper (Lepidocolaptes souleyetii) and the fasciated wren (Campylorhynchus fasciatus). The levels of nest parasitism found were much lower than levels reported for the Galápagos Islands. Finally, parasitism of P. downsi by a parasitoid in the genus Brachymeria (Hymenoptera, Chalcididae) is documented. Overall, 9% of fly puparia collected in 2013, and 19% of those collected in 2014, had parasitoid emergence holes.